Developing Expert Principals - Darling-Hammond, Linda; Wechsler, Marjorie E.; Levin, Stephanie; Leung-Gagné, Melanie; Tozer, Steven; Kee Campoli, Ayana (Taylor & Francis, 2025)
Strong school leadership is critical for shaping engaging learning environments, supporting high-quality teachers and teaching, and influencing student outcomes. Developing Expert Principals offers a comprehensive research synthesis to understand the elements of high-quality programs and learning experiences that have been associated with positive outcomes ranging from principals’ preparedness and practices to staff retention and student achievement. This book also offers vivid examples of high-quality programs and examines the extent to which principals have opportunities to participate in effective learning experiences. It examines the policies that drive both the development of high-quality programs and access to them, highlighting successful examples across the country. With practical recommendations throughout, this book is a key resource for educational leaders, faculty and scholars of educational leadership, developers of leadership preparation and training, and policymakers who seek to create a learning system that will better serve principals, the staff they support, and, ultimately, all children. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial (CC-BY-NC) 4.0 license.